The Role of Organizational Prowess on Organizational Citizenship Behaviors An analytical study of the views of a sample of academic staffs in the Knowledge University in the Erbil city - Ahmed , Sardar Abdulhameed; Sadq, Zana Majed; Omar , Sherwan Omer (Zanco Journal of Human Sciences, 2021)
The research aims to measure and illustrate the effect and relationship between organizational ambidexterity including its dimensions (Exploitation ambidexterity, exploration ambidexterity, flexible organizational structure ambidexterity) and organizational citizenship behavior in Knowledge University in Erbil City in Iraqi Kurdistan Region. This research presents several questions which depicts the problem of the research. Questionnaire was designed as a data collection method in order to meet the research objectives and to test the main hypotheses of the research. Research sample were selected randomly through distributing the questionnaire among teaching staff. (50) questionnaires were distributed and (48) questionnaires were returned. (47) questionnaires were valid to run statistical analysis. The results of the research revealed: the perceptions level of the respondents about implementing organizational ambidexterity (Exploitation ambidexterity, exploration ambidexterity, flexible organizational structure ambidexterity) in Knowledge University in Erbil City were high. With regard to implementing the concept of organizational citizenship behavior (altruism, courtesy, sportsmanship, conscientiousness, civic virtue) in Knowledge University in Erbil City, the perceptions of respondents were moderate and high. The research found that there is a significant effect and relationship between organizational ambidexterity and organizational citizenship behavior. In light of these results, several recommendations were formulated to the investigated organization including; the continues of illustrating the importance of employee’s perceptions in organizational ambidexterity organizations and organizational citizenship behavior within its different dimensions that reflect positively on job performance and thus organizational performance.